Asociación del control prenatal de calidad y la depresión post parto en puérperas atendidas en el Hospital Regional de Loreto, 2022 - Guzmán León, Nataly Graciela (2023)
Childbirth is a difficult and exhausting process, a woman goes through many hormonal, physical, emotional and psychological changes during pregnancy. Adequate prenatal care during pregnancy is of vital importance to reduce maternal and child morbidity and mortality, in addition to helping early identification of depression. For this reason, the present work aims to determine the association between quality prenatal control and postpartum depression in puerperal women treated at the Loreto Regional Hospital, 2022. For this, an observational-analytical and cross-sectional study was developed, as an instrument used the Edinburgh Postnatal Depression Scale, had 186 puerperal women as a sample. It was observed that 52.7% of the mothers presented postpartum depression, 34.9% of the mothers did not present quality prenatal control and it was concluded that there is a statistically significant association between not having quality prenatal controls and suffering from postpartum depression (p< 0.001).